DEVELOPING SEMANTIC NETWORK MANAGEMENT SYSTEM - Semchyshyn, Yuriy; Kulpa, Ivan; Kolosovskyi, Igor; Hrechnikov, Oleksandr; Hayda, Petro (International Journal of Computing, 2014)
The paper considers semantic networks. It is a way of representing knowledge as a set of nodes-concepts connected by edges-relations. The history and current state-of-the-art of semantic networks is analyzed. The experience of designing and developing semantic network management system is described in four sections covering the following topics: data structures design, semantic analysis algorithm implementation, graph visualization methods selection and Web-based user interface development. The developed system is fully-operational tool for building and studying semantic networks. The system will be used for the further research.